THE PECULIAR NATURE OF APPLICATION OF BUSINESS AND LEGAL LIABILITY UNDER EFFECTIVE LEGISLATION OF UKRAINE - Horbatiuk, Yana V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the paper provides an overview of the approaches, existing in scientific world of Business Law, toward construction of the business and legal liability notion and identifies the lack of such definition in the Commercial Code of Ukraine. Methods: phenomenological; hermeneutic; comparative-legal; sociological; logical; dialectical. Results: in the course of the study, there have been defined the principles, limits and subjects of application of business and legal liability, there has been set out the possibility to exercise application of the pre-trial procedure for business and legal liability, envisaged by the legislation. The author also establishes factual and legal basis for application of business and legal liability. Discussion: the paper examines the rules of the Constitution of Ukraine with regard to impossibility to hold a person legally liable through the prism of the rules of the Commercial Code of Ukraine and states the fact of existence of a certain collision in this situation.